PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN: (Studi pada Konsumen PT. Duta Teknologi Nusantara di Tangerang Kota) - Desti Anasari; Ravindra Safitra Hidayat (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This research aims to analyze the influence of price perceptions, product quality and service quality on purchasing decisions (Study on consumers of PT. Duta Teknologi Nusantara in Tangerang City). The data source used in this research is primary data by distributing questionnaires. The population of this research is consumers of PT. Archipelago Technology Ambassador. The sample in this study used the Slovin formula method and obtained 96 respondents. The analysis tool used is SPSS v.25 software. The results of this research show that price perception and service quality have a significant effect on purchasing decisions at PT Duta Teknologi Nusantara, while product quality has no effect on PT Duta Teknologi Nusantara's purchasing decisions. Archipelago Technology Ambassador.